Hubungan Frekuensi Konsumsi Fast food Dengan Kejadian Hipertensi Pada Usia Produktif Di Wilayah Kerja Puskesmas Kediri I - Peronika Hida Hona; Ni Wayan Udayani; Ari Wina Sani (LPPM STIKES Mataram, 2026)
Introduction: Hypertension is a chronic condition characterized by persistently elevated blood pressure and is a major risk factor for cardiovascular diseases. One factor suspected to be associated with hypertension is the consumption of fast food, which generally contains high levels of sodium, saturated fat, and calories. The increasing consumption of fast food among individuals of productive age may contribute to a higher risk of developing hypertension. Objective: This study aimed to determine the relationship between the frequency of fast food consumption and the incidence of hypertension among productive-age adults in the working area of Kediri I Public Health Center, Tabanan Regency. Method: This study employed an analytical observational design with a cross-sectional approach. A total of 106 respondents were selected using a consecutive sampling technique. Data were analyzed using the Chi-Square test with a significance level of 0.05. Results: The results showed that respondents who frequently consumed fast food tended to have higher blood pressure categories compared to those who did not frequently consume fast food. Statistical analysis using the Chi-Square test yielded a p-value of 0.001 (p < 0.05), indicating that H₀ was rejected and H₁ was accepted. Conclusion: There was a significant relationship between the frequency of fast food consumption and the incidence of hypertension among productive-age adults in the working area of Kediri I Public Health Center, Tabanan Regency.